Business ethics in developing countries - Rossouw, G. J. (Koers, 1992)
Underlying this paper is the conviction that it is of the utmost importance that business ethics should indeed become an integral part of business culture in all, and therefore also in developing countries. It is not to be denied that business ethics has to a much larger extent become pari of the business culture' in developed countries than in developing countries. The primary aim of this paper is to provide an explanation for the fact that business ethics is fighting an uphill battle in becoming pari of the business culture in developing countries. Secondly, a thumbnail sketch is given of the preconditions that have to be fulfilled in order to stimulate the development of a moral business culture in developing countries. In order to achieve these goals I will focus mainly on Africa, and more specifically on South Africa.